Analisis Penerapan Tanda Tangan Elektronik Pada Tata Naskah Dinas Elektronik (Attandie) Di Direktorat Jenderal Kependudukan Dan Pencatatan Sipil - Risya Amalia; Arih Setyaningrum; Evi Satispi (International Forum of Researchers and Lecturers, 2023)
The existence of technology has become insignificant and affects all activities and human life in the world. As in today's era, almost everything is dependent on technology. Information technology in the e-government era can make it easy for people to obtain information and communicate interactively. Because with this technology, we can get information quickly. Information obtained through communication technology makes it easier for an organization to cooperate with each other in achieving the goals of the organization. Therefore the use of technology needs to be optimized and developed so as not to experience backwardness in obtaining information. This study aims to analyze the application of electronic signatures to the electronic official document system at the Jakarta Directorate General of Population and Civil Registration using qualitative research methods by collecting data through recording and observation. The theory used is Grindle's policy implementation theory. Based on the results of the research and discussion above, it can be concluded that the application of electronic signatures to the electronic official document system at the Directorate General of Population and Civil Registration in Jakarta in general has a positive impact and eases the work of its employees.